Mindfulness-based programs and school adjustment: A systematic review and meta-analysis. (April 2023) - Mettler, Jessica; Khoury, Bassam; Zito, Stephanie; Sadowski, Isabel; Heath, Nancy L.
Abstract: Mindfulness-based programs (MBPs) are increasingly used in educational institutions to enhance students' mental health and resilience. However, reviews of the literature suggest this use may have outpaced the evidence base and further research is needed to better understand the mechanisms underlying these programs' effectiveness and which outcomes are being affected. The purpose of this meta-analysis was to investigate the strength of MBPs' effects on school adjustment and mindfulness outcomes while also considering the potential influence of study and program characteristics, including the role of comparison groups, students' educational level, the type of program being used, and the facilitator's training and previous mindfulness experience. Following a systematic review of five databases, 46 studies using a randomized controlled design with students from preschool to undergraduate levels were selected. At post-program, the effect of MBPs compared to control groups was (a) small for overall school adjustment outcomes, academic performance, and impulsivity; (b) small to moderate for attention; and (c) moderate for mindfulness. No differences emerged for interpersonal skills, school functioning, or student behaviour. The effects of MBPs on overall school adjustment and mindfulness differed based on students' educational level and the type of program being delivered. Moreover, only MBPs delivered by outside facilitators with previous experience of mindfulness had significant effects on either school adjustment or mindfulness. This meta-analysis provides promising evidence of the effectiveness of MBPs in educational contexts to improve students' school adjustment outcomes beyond typically assessed psychological benefits, even when using randomized controlled designs. Highlights: International meta-analysis reveals importance of mindfulness for school adjustment. Identified benefits for attention, academics, impulsivity, and mindfulness. Differential benefits based on students' educational level. Effectiveness enhanced by outside facilitator with mindfulness experience. Adapted mindfulness-based programs showed broadest impact.